AgriTech4Morocco Innovation Challenge Bootcamp Report - Menza, Gianpiero; Zaccari, Claudia (2023)
The AgriTech4Morocco Innovation Challenge is an initiative designed by the CGIAR Accelerate for Impact Platform (A4IP), funded by Digital Development Partnership administered by the World Bank, and implemented with the support of Impact Lab. The project benefits from the support offered by GIZ, the Moroccan Ministry of Agriculture, Maritime Fisheries, Rural Development and Water and Forests, and le Pôle d’Agriculture Digitale. The objective of the AgriTech4Morrocco Innovation Challenge is to scout, select, and accelerate solutions operating in the agri-tech space aimed at enhancing efficiency, equity, and environmental sustainability for Morocco while aligning with the Generation Green 2020-2030 Strategy. The one-month call for applications attracted over 360 applications from 31 countries. An intensive three-day bootcamp for the AgriTech4Morocco Innovation Challenge was organized for the 20 shortlisted projects. The bootcamp was held on the campus of Le Qualipôle Alimentation in Meknès, Morocco, an agri-food innovation center with extensive facilities on 23-25 May. The goal of the bootcamp was to support innovators to understand the existing opportunities of the Moroccan agri-food ecosystem, refine their business model and pitch, explore new partnerships, and develop their entrepreneurial skills to scale for positive impact through expert talks, workshops, and one-on-one coaching. Thirty-two participants belonging to 19 teams, actively took part in the bootcamp, representing entrepreneurs, researchers, and students from 11 countries spanning across Africa, Europe, the Middle East, and Americas. The Selection Committee – comprising partner representatives and sector experts – also joined bootcamp participants and organizers for the Pitch Day on Wednesday, 25 May. Eighteen innovation teams pitched their projects to the Selection Committee, who conducted an assessment based on six criteria that included the project quality, relevance to the context of Morocco and Generation Green 2020-2030 Strategy, the sustainability and scalability of the project in terms of its revenue model, its scientific relevance, the market readiness and maturity, and the quality of the team.